E-Banking Services and Customer Satisfaction of Nepalese Commercial Banks - Adhikari, Shiva Raj (The Mega Journal, 2025)
Purpose: The study investigates the impact of electronic banking services on customer satisfaction in Nepalese commercial banks, focusing on five dimensions: convenience, cost advantage, secure services, ease of use, and personalization & customization. Methods: A survey of 400 e-banking users was conducted. Variables were selected based on a comprehensive literature review and analyzed using statistical tools, including descriptive analysis, correlation, regression, reliability tests, and ANOVA through SPSS. Demographic factors such as gender, age, marital status, education, profession, and income were also examined. Findings: There is a significant positive relationship between customer satisfaction and the dimensions of convenience, security, ease of use, and personalization. Cost advantage had no significant effect. Among all factors, convenience was identified as the most influential in enhancing customer satisfaction. Implications: The results emphasize the need for Nepalese commercial banks to prioritize user friendly, secure, and personalized e-banking services, as these aspects are more valued by customers than mere cost benefits. These insights can guide the development of customer-centric services in a competitive market.